Sistem Pendukung Keputusan Pemilihan Diet terhadap Penderita Penyakit Jantung Menggunakan Metode TOPSIS - Vicky Hotty Setya Hanitha; Erick Dazki (G-Tech: Jurnal Teknologi Terapan, 2023)
People with heart disease are often advised to go on a diet, but not a few are confused about what kind of diet to choose considering the many taboos that sufferers must undergo and there are various types of diets. Knowing this, the decision support system is one of the efforts to help people with heart disease choose the right diet. This system uses a method that is commonly used in decision support systems, namely the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method which is able to identify solutions from a set of options based on trimming the distance to the ideal point and optimizing the distance from the lowest point. The results of this study were found that the best diet for people with heart disease is the Zone Diet with a preference value of 1, compared to other types of diets, namely the Atkins Diet, Keto Diet and Vegan Diet.